2002
DOI: 10.1248/bpb.25.642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,25-Dihydroxyvitamin D<sub>3</sub> [1,25(OH)<sub>2</sub>D<sub>3</sub>] and Its Analogues (EB1089 and Analog V) on Canine Adenocarcinoma (CAC-8) in Nude Mice

Abstract: Recently the active form of vitamin D, 1a,25-dihydroxyvitamin D 3 , [1,25(OH) 2 D 3 ] and its synthetic analogues have been shown to exert anti-tumor effects both in vitro and in vivo. [1][2][3][4][5] As summarized by Johannes et al.,6) many investigations have reported that 1,25(OH) 2 D 3 and its analogues affect tumor cells due to: a) blockade of the cells in the G 1 /G 0 phase and reduction of the number of cells in S phase of cell cycle progression, 7-9) b) induction of apoptosis, 10,11) c) expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In canine species, the VDR expression has been shown on the majority of the mast cell tumours and osteosarcomas . Vitamin D metabolites have been shown to have in vitro anti cancerous effects on canine cancer cell lines, with some evidence of in vivo efficacy …”
Section: Introductionmentioning
confidence: 99%
“…In canine species, the VDR expression has been shown on the majority of the mast cell tumours and osteosarcomas . Vitamin D metabolites have been shown to have in vitro anti cancerous effects on canine cancer cell lines, with some evidence of in vivo efficacy …”
Section: Introductionmentioning
confidence: 99%
“…In addition, an increased relative risk (RR) for cancer was observed as serum 25(OH)D levels decreased; therefore, the RR of cancer for 25(OH)D below 40 ng/ml of all-cancer group and of HAS group were 3.9 and 4.1, respectively, compared with that of the control group. In contrast,Willcox, Hammett-Stabler, and Hauck (2016) found no difference in serum concentrations of 25(OH)D in 20 dogs affected by osteosarcoma, compared with a control group matched for age and body weight.Studies have demonstrated in vitro antineoplastic effects of calcitriol for various types of canine tumours, including osteosarcoma(Barroga, Kadosawa, Okumura, & Fujinaga, 1999), squamous cell carcinoma(Kunakornsawat et al, 2001), prostatic epithelial tumour(Kunakornsawat et al, 2004), anal sac adenocarcinoma(Kunakornsawat et al, 2002), mammary gland cancer(Rassnick et al, 2008) and mastocytoma(Malone et al, 2010). These findings reinforce the hypothesis that low concentrations of vitamin D may increase the risk of developing cancer.…”
mentioning
confidence: 74%
“…Wakshlag et al (2011) evaluated the relationship between serum concentrations of 25(OH)D and mastocytoma in Labrador Retrievers.In total, 33 animals affected by this disease were evaluated and compared with a control group that was composed of 54 healthy animals, and lower serum concentrations 25(OH)D were observed in dogs with mastocytoma.In another study conducted bySelting et al (2016), the 25(OH) D serum concentrations from a group of healthy dogs (control group; n = 282) were compared to 25(OH)D serum concentrations from a group of dogs with splenic malignancies (all-cancer group; n = 40) and with another group of dogs with benign neoplasms (benign group; n = 22). In contrast,Willcox, Hammett-Stabler, and Hauck (2016) found no difference in serum concentrations of 25(OH)D in 20 dogs affected by osteosarcoma, compared with a control group matched for age and body weight.Studies have demonstrated in vitro antineoplastic effects of calcitriol for various types of canine tumours, including osteosarcoma(Barroga, Kadosawa, Okumura, & Fujinaga, 1999), squamous cell carcinoma(Kunakornsawat et al, 2001), prostatic epithelial tumour(Kunakornsawat et al, 2004), anal sac adenocarcinoma(Kunakornsawat et al, 2002), mammary gland cancer(Rassnick et al, 2008) and mastocytoma(Malone et al, 2010). The control group presented higher 25(OH)D serum concentrations when compared to all other groups.…”
mentioning
confidence: 99%
“…1,25 dihydroxyvitamin D has been shown to have in vitro anti cancerous effects on other canine cancer cell lines, with some evidence of in vivo efficacy (Kunakornsawat et al . , Kaewsakhorn et al . , Rassnick et al .…”
Section: Vitamin D – An Overviewmentioning
confidence: 99%